PENGARUH PENERAPAN TEKNIK TOKEN ECONOMY TERHADAP TOILET TRAINING PADA ANAK USIA 2-3 TAHUN DI TPA IT FUTURE ISLAMIC SCHOOL KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Nike Azlina; Daviq Chairilsyah; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aims of this research to know the influence application of token economy techniques to toilet training 2-3 years old children at Day Care IT Future Islamic School Kecamatan Payung Sekaki Pekanbaru City. The samples in this study are children aged 2-3 years in Day Care IT Future Islamic School Payung Sekaki District Pekanbaru City. The sample in this research are 5 childrens. The method used is experimental method to find the influence of token economy technique to toilet training. Data collection techniques used are observation and assisted by observation sheet. Data analysis technique used t-test with SPSS 17.0 program. The research hypothesis is the application of token economy techniques have an influence on the success of toilet training at age-3 years in Day Care IT Future Islamic School Payung Sekaki District Pekanbaru City. This can be known from the analysis of data obtained zhitung = 2.032 and Sig. (2-tailed) = 0.042. Because Sig. (2-tailed) = 0,04 <0,05 it can be concluded that there is difference of children toilet training ability significantly after application of token economy technique in learning. So it means Ho is rejected and Ha accepted which means there is a very significant difference between before and after doing experiments by applying token economy technique. The influence of the application of token economy technique to toilet training 2-3 years old children in TPA IT Future Islamic School Payung Sekaki District, Pekanbaru City is 35.5%.Keywords: Toilet Training, Application of Token Economy Technique